Fifty fifty : an Eddie Flynn novel - Cavanagh, Steve (Cavanagh, Steve. Eddie Flynn novel, 2025)
"Alexandra Avellino has just found her father's mutilated body, and needs the police right away. She believes her sister killed him, and that she is still in the house with a knife. Sofia Avellino has just found her father's mutilated body and needs the police right away. She believes her sister, Alexandra did it, and that she is still in the house, locked in the bathroom. Both women are to go on trial at the same time. A joint trial in front of one jury. But one of these women is lying. One of them is a murderer. Sitting in a jail cell, about to go on trial with her sister for murder, you might think that this is the last place she expected to be. You'd be wrong"--